A case of giant nipple adenoma - Shuko Ono; Masumi Tanaka; Yasuteru Yoshinaga; Toshihiko Satou; Mikiko Aoki (Surgical Case Reports)
Abstract Background Nipple adenoma is a relatively rare benign disease. Clinically, it often presents with nipple erosions, and it should be differentiated from Paget’s disease. Case presentation The patient was a 63-year-old woman who complained of a lump in her left nipple for more than 30 years. Computed tomography performed for screening congestive heart failure suggested a left nipple mass of 40 mm in size. Needle biopsy revealed nipple adenoma, and skin biopsy was also performed to confirm the diagnosis. Nipple tumor resection was performed under local anesthesia, and we confirmed that the final diagnosis was nipple adenoma with negative margins. The patient has been free from recurrence for 2 years since the surgery. Conclusions We have reported our experience of a case of giant nipple adenoma.